Single Nucleotide Polymorphisms in IFN-γ Signaling Pathway Associated with Risk of Hepatitis B Virus Infection in Chinese Children - Yang Zhuo; Yalan Yang; Mingjun Zhang; Ying Xu; Zhongping Chen; Lihong Mu; Xiaojun Tang; Zhaohui Zhong; Juan Chen; Li Zhou (Canadian Journal of Infectious Diseases and Medical Microbiology)
Hepatitis B virus (HBV) infection is a challenging public health problem in China and worldwide. Mother-to-child transmission is one of the main transmission routes of HBV in highly endemic regions. However, the mechanisms of HBV perinatal transmission in children have not been clearly defined. The aim of this study was to demonstrate the association between single-nucleotide polymorphisms (SNPs) in IFN-γ signaling pathway and HBV infection or breakthrough infection in children. Two hundred and seventy-four HBV-infected children defined as test positive for hepatitis B surface antigen (HBsAg) and 353 controls defined as negative for HBsAg in China were recruited from October 2013 to May 2015. SNPs in IFN-γ signaling pathway including IFNG, IFNGR1, IFNGR2, and IL12B were genotyped. Rs2234711 in IFNGR1 was significantly associated with HBV infection in children (OR = 0.641, 95% CI: 0.450–0.913). In addition, rs2234711 was also significantly associated with HBV breakthrough infection in children born to HBsAg-positive mothers (OR = 0.452, 95% CI: 0.205–0.998). Our study confirmed that genetic variants in IFN-γ signaling pathway have significant associations with HBV infection, especially with HBV breakthrough in children. This study provides insight into HBV infection in children and could be used to help design effective strategies for reducing immunoprophylaxis failure.